MODELLING THE TRANSPORT PROBLEM OF RESOURCES FROM DIFFERENT SOURCES BY MEANS OF LINEAR PROGRAMMING - Алтухова, Тетяна; Сергієнко, Людмила; Сергієнко, Олександр (SWorldJournal, 2025)
This paper considers the issue of optimising transport costs based on linear programming. This is due to the fact that linear programming has an extremely wide range of practical applications in decision theory, operations research and optimal planning.